2019
DOI: 10.21307/pjm-2019-002
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Gamma Release Assays in Patients with Respiratory Isolates of Non-Tuberculous Mycobacteria – a Preliminary Study

Abstract: Interferon gamma releasing assays (IGRAs) are extensively used in the diagnosis of latent tuberculosis infections. Comparing to tuberculin skin test (TST) they lack false positive results in the populations vaccinated with BCG, and in most non-tuberculous mycobacteria (NTM) infections. Nevertheless, Mycobacterium kansasii, Mycobacterium marinum, and Mycobacterium szulgai may induce positive IGRAs due to RD1 homology with Mycobacterium tuberculosis. The aim of the study was to investigate the possible influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
(1 reference statement)
1
12
0
Order By: Relevance
“…So, most of NTM infection could have negative results. In our study, a negative test for QFT is more common in NTM patients, it was also found in other studies, 16,17 and through our multivariate regression analysis, it was found an independent risk factor for predicting NTM, which might be an important factor for differential diagnosis.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…So, most of NTM infection could have negative results. In our study, a negative test for QFT is more common in NTM patients, it was also found in other studies, 16,17 and through our multivariate regression analysis, it was found an independent risk factor for predicting NTM, which might be an important factor for differential diagnosis.…”
Section: Discussionsupporting
confidence: 87%
“…Meanwhile, 17.2% of NTM patients presented positive QFT results in our investigation. As we know, IGRAs are specific for M. tuberculosis and not encoded in the genomes of any Bacillus Calmette–Guerin (BCG) vaccine strains or most species of NTM, other than M. marinum , M. kansasii , M. szulgai and M. flavescens 16 . However, not all NTMs have been studied for cross‐reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, some NTM species ( M. kansasii , M. marinum and M. szulgai ) sharing RD1 with M. tuberculosis showed similar positive results with IGRAs as M. tuberculosis ( Hermansen et al., 2014 ; Chen et al., 2018 ; Augustynowicz-Kopeć et al., 2019 ), and the feasibility of differentiating these species from PTB was doubtful. Our analysis suggested there was no statistically significant difference of IGRAs performances between any species of NTM.…”
Section: Discussionmentioning
confidence: 99%
“…Hermansen reported the QFT-G positivity rate was 8% (4/53) in definite NTM disease and 31% (15/49) in possible disease with colonization, while the overall rate of positive QFT-G in pulmonary NTM disease defined patients was 18% (81/462) by their systematic review ( Hermansen et al., 2014 ). Augustynowicz-Kopeć reported that the positive IGRAs result was 8% in NTM definite patients (3/39) ( Augustynowicz-Kopeć et al., 2019 ). Wang stated that the positivity rate of T-SPOT.TB was 53.4% (31/58) among the probable and definite NTM groups, 53.5% (15/28) for probable cases and 53.3% (16/30) for definite cases ( Wang et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…A similar observation was made by Moon et al (2016) , who found past lung tuberculosis in 64% of patients with M. chimaera infection. The other NTM type often responsible for NTMLD in patients with post-tuberculous lung lesions is Mycobacterium kansasii ( Augustynowicz-Kopeć et al 2019 ). It is not known whether the higher incidence of NTMLD in those NTM-infected patients, who had a history of past tuberculosis, is related to the favorable conditions for their colonization in the altered lung parenchyma, or a defect in the intracellular killing of NTM in these patients.…”
Section: Discussionmentioning
confidence: 99%